Global regulations and practices for well integrity management: a review - Marcel Schulz; Mayukh Talukdar; Isabelle Pfander; Greg Lackey; Luisa Röckel; Andrew Wojtanowicz; Frank Schilling; Philipp Blum (Journal of Petroleum Exploration and Production Technology)
Abstract The integrity of oil and gas wells ensures safe operations and preserves air and water quality. Thus, it is important to identify and repair well integrity issues that cause unwanted gas movement within a well system. Sustained casing pressure (SCP) and surface casing vent flow (SCVF) are key well integrity indicators. This study presents the first review of SCP/SCVF government regulations and industry guidelines across major oil- and gas-producing countries, including the USA, Canada, Australia, Norway, Russia, and China. Regulations vary widely: the USA, Canada, and Russia have specific regulatory requirements, while Australia and Norway leave more responsibility to operators. China relies on guidelines from state-owned companies. Major oil- and gas-producing provinces in Canada require pressure to be released to the atmosphere as SCVF. The U.S. industry guideline API RP 90 underpins offshore SCP regulations in multiple countries, but no global standard exists. Routine annulus pressure or flow monitoring is required in 38% of U.S. states, 15% of Canadian provinces and territories, as well as in Norway and Russia, whereas China and Australia do not have such requirements. Diagnostic testing for SCP or SCVF is required in 12% of U.S. states, 38% of Canadian provinces and territories, and Russia. However, testing is not mandated in China, Australia, and Norway. This study proposes a minimum standard workflow that can be included and adjusted in jurisdictions without SCP/SCVF regulations. The proposed workflow includes routine monitoring, diagnostic testing when anomalies occur, and remediation, providing a structured approach to well integrity management.